County and City Data Book (United States), 1983 ([Verlag nicht ermittelbar], 1984)
This data collection consists of three data files: a counties file, a cities file, and a places file. The Counties File (Part 1) provides data on area and population, households, vital statistics, health, Social Security, Supplemental Security Income, crimes, housing, journey to work, education, labor force, personal income, money income, government employment and finances, manufactures, wholesale and retail trade, service industries, banking, elections, and agriculture. It provides data for the nation as a whole, the 50 states, the District of Columbia, and 3,137 counties or county equivalents. There are two physical records (segments) of 1,276 characters for each of the conceptual records in the counties file. Records are sequenced by FIPS state code and, within that, FIPS county code. The Cities File (Part 2) includes, in addition to most of the subjects in the counties file, data on workers in the family, climate, and residential electric bills. The cities file provides data for the 50 states and the District of Columbia and for 957 incorporated cities with 25,000 inhabitants or more in 1980. The sequence of records is FIPS state code and, within that, Census place code. Part 3, the Places File, provides data on land, population, money income, and households. It includes data for the 50 states, District of Columbia, 7,601 places with 2,500 inhabitants or more in 1980, and, for 11 states, 2,368 minor civil divisions (MCDs) with 2,500 inhabitants or more in 1980. Records are sequenced by FIPS state code and, within that, Census place code. For the 11 states for which MCDs are shown, the MCD records follow the place records, which are sorted alphabetically within the state.